Production of human milk fat substitutes by interesterification of tripalmitin with ethyl oleate catalyzed by candida parapsilosis lipase/acyltransferase - Tecelão, Carla (2020)
In human milk fat, the saturated fatty acids,namely palmitic acid, are located at the sn-2 position of triacylglycerols (TAG) while unsaturated fatty acids (e.g. oleic acid) are esterified at position sn-1,3. Thus, sn- 1,3-dioleoyl-2-palmitoylglycerol (OPO) is the target TAG to be used as human milk fat substitutes (HMFS) in infant formulas. In this study, the noncommercial recombinant lipase/acyltransferase from Candida parapsilosis (CpLIP2) was immobilized in Accurel MP1000, and used as a biocatalyst for the interesterification of tripalmitin with ethyl oleate in a solvent-free medium, to obtain structured lipids used as HMFS. Different molar ratios (MR) of ethyl oleate to tripalmitin (2:1–8:1) were used. After 4 h reaction at 60ºC, about 30 mol% of oleic acid incorporation was already observed for all tested MR. An apparent equilibrium was reached after 8–24 h, with 32–51 mol% final incorporation, increasing with the MR. The incorporation of oleic acid into TAG was compared with the maximum predicted values when a random or a sn-1,3-regioselective biocatalyst was used. The obtained values are consistent with the maximum incorporation expected for a sn-1,-3-regioselective enzyme. In fact, the amount of oleic acid at position sn-2 was approximately 15% for all the MR tested, which is explained by the acyl migration phenomenon. CpLIP2 exhibited higher activity than most commercial immobilized lipases (e.g. faster reaction in solvent-free media, low enzyme load, and low MR needed), and showed a recognized sn-1,3 regioselective behavior.